Exploring the relationship between secondary science teachers' subject matter knowledge and knowledge of student conceptions while teaching evolution by natural selection. Issue 2 (31st August 2016) - Lucero, Margaret M.; Petrosino, Anthony J.; Delgado, Cesar
Abstract: The fundamental scientific concept of evolution occurring by natural selection is home to many deeply held alternative conceptions and considered difficult to teach. Science teachers' subject matter knowledge (SMK) and the pedagogical content knowledge (PCK) component of knowledge of students' conceptions (KOSC) can be valuable resources for helping students learn difficult science concepts such as natural selection. However, little research exists that explores the relationship between science teachers' SMK and their KOSC on evolution by natural selection. This study explores the relationship between SMK and KOSC through the participation of four biology teachers at a single high school and thus deepens our understanding of the teacher knowledge base. Main data sources are teacher interviews in which each teacher answered SMK‐type questions and predicted what their students' most common alternative conceptions were by using the Conceptual Inventory of Natural Selection (CINS). Other data sources include student responses on the CINS and classroom observations. Findings revealed relative independence between SMK and KOSC, although there is likely a minimum threshold of SMK to recognize student alternative conceptions. However, our work also revealed ways in which teachers were not leveraging their KOSC and suggest potential avenues for future inquiry. © 2016 Wiley Periodicals, Inc. J Res Sci Teach 54: 219–246, 2017